Kandungan Hukum Islam Dalam Ayat-Ayat Mutasyabihat - Ruslan Ruslan (JOURNAL OF ISLAMIC AND LAW STUDIES, 2022)
Abstract: The study of mutasyabihat verses in relation to Islamic law looks rather unusual. This is because the assumption built by the scholars is "the mutasyabihat verses concentrate more on the field of aqidah (al-ahkam al-I'tiqadiyah)". Meanwhile, the verses regarding halal-haram law include the muhkamat verse (the meaning is clear); as opposed to the mutasyabihat verse. This paper attempts to present the content of Islamic law (shara' law) in mutasyabihat verses. The result actually strengthens the existence of mutasyabihat verses on musykil, musytarak, and mubham pronunciations. The themes of the verse become clearer when viewed with a substantive approach, for example the law of marriage polygamy, the tradition of destroying the back wall of the house after Umrah or Hajj, the law against polytheists, the meaning of quru' for women who have lost their husbands, the law on coalitions of Muslims and non-Muslims. , and others tend to say that the legal verses are actually more mutasyabihat. The aim is allegedly to strengthen faith in Allah and so that the universality of the Qur'an is maintainedÂ Abstrak: Kajian tentang ayat-ayat mutasyabihat dalam hubungannya dengan hukum Islam terlihat agak tidak lazim. Hal ini karena asumsi yang dibangun para ulamaÂ Â  â€œayat-ayat mutasyabihat lebih berkonsentrasi pada bidang akidah (al-ahkam al-Iâ€™tiqadiyah)â€. Sementara ayat-ayat tentang hukum halal â€“ haram termasuk ayat muhkamat (jelas maknanya); sebagai lawan ayat mutasyabihat. Tulisan ini berusaha mengemukakanÂ  kandungan hukum Islam (hukum syaraâ€™) dalam ayat-ayat mutasyabihat. Hasilnya justuru menguatkan adanya ayat-ayat mutasyabihatÂ  pada lafal-lafal musykil, musytarak, dan mubham. Tema-tema ayat pun menjadi lebih jelas ketika dilihat dengan pendekatan substantif misalnya hukum poligami perkawinan, tradisi merusak tembok belakang rumahÂ  setelahÂ  umrah atauÂ  haji, hukum memerangi orang musyrik,Â  makna quruâ€™ bagi wanita yang ditinggal mati suami, hukum koalisi muslim dan non-muslim,Â  dan Â lain- lain cenderung dikatakan ayat-ayat hukum justru lebih banyak mutasyabihatnya. Tujuannya diduga untuk mengokohkan keimanan kepada Allah dan agar universalitas AlquranÂ  tetap terpelihara